COMMATRIOTS IN THE YEARS OF THE SECOND WORLD WAR ABOUT WARRIOR'S SPIRIT AND HEROISM (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article contains thoughts and comments about the great common contribution of our people to the victory over fascism, the courage, tenacity, courage and heroism shown by the hero of Uzbekistan, Mamadali Topiboldiev, in the battles.